Given that a <span>store is selling two mixtures of nuts in 20-ounce bags: peanuts and cashews.
Let the cost of one ounce of peanut be x and the cost of one ounce of cashew be y, then
Given that </span>t<span>he first mixture has 15 ounces of peanuts combined with five ounces of cashews, and costs $4.25 implies that 15x + 5y = 4.25
Also, given that </span>t<span>he second mixture has five ounces of peanuts and 15 ounces of cashews, and costs $6.75 mplies that 5x + 15y = 6.75
To obtain the cost of </span><span>one ounce of peanuts and one ounce of cashews, we solve the two equations above, simultaneously:
![15x + 5y = 4.25 - - - (1) \\ 5x + 15y = 6.75 - - - (2) \\ \\ (1)\times3\Rightarrow45x+15y=12.75 - - - (3) \\ \\ (2)-(3)\Rightarrow-40x=-6 \\ \\ \bold{x= \frac{-6}{-40} =0.15} \\ \\ From\ (1):15(0.15)+5y=4.25 \\ \\ 5y=4.25-2.25=2 \\ \\ \bold{y= \frac{2}{5} =0.4}](https://tex.z-dn.net/?f=15x%20%2B%205y%20%3D%204.25%20-%20-%20-%20%281%29%20%5C%5C%205x%20%2B%2015y%20%3D%206.75%20-%20-%20-%20%282%29%20%5C%5C%20%20%5C%5C%20%281%29%5Ctimes3%5CRightarrow45x%2B15y%3D12.75%20-%20-%20-%20%283%29%20%5C%5C%20%20%5C%5C%20%282%29-%283%29%5CRightarrow-40x%3D-6%20%5C%5C%20%20%5C%5C%20%5Cbold%7Bx%3D%20%5Cfrac%7B-6%7D%7B-40%7D%20%3D0.15%7D%20%5C%5C%20%20%5C%5C%20From%5C%20%281%29%3A15%280.15%29%2B5y%3D4.25%20%5C%5C%20%20%5C%5C%205y%3D4.25-2.25%3D2%20%5C%5C%20%20%5C%5C%20%5Cbold%7By%3D%20%5Cfrac%7B2%7D%7B5%7D%20%3D0.4%7D%20)
Therefore, </span><span>
one ounce of peanuts and one ounce of cashews cost $0.15 and $0.40 respectively.</span>
Answer: I got -8/9. Hope this helps in any way shape of form.
Step-by-step explanation:
Answer:
I belive the answer is 5
Step-by-step explanation:
Answer:
Perimeter of the smaller triangle = 1.75x
Step-by-step explanation:
Let the two equal sides of an isosceles triangle = x
Therefore, length of the base = ![(1\frac{1}{2})x](https://tex.z-dn.net/?f=%281%5Cfrac%7B1%7D%7B2%7D%29x)
Perimeter of this isosceles triangle = x + x + ![(1\frac{1}{2})x](https://tex.z-dn.net/?f=%281%5Cfrac%7B1%7D%7B2%7D%29x)
= 2x + ![(1+\frac{1}{2})x](https://tex.z-dn.net/?f=%281%2B%5Cfrac%7B1%7D%7B2%7D%29x)
= 2x + x + ![\frac{x}{2}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7B2%7D)
= ![\frac{5x}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B5x%7D%7B2%7D)
Since, smaller triangle has a perimeter that is half the perimeter of the larger triangle,
Length of each corresponding side of smaller triangle will be half of the larger triangle.
Length of sides of the smaller triangle = ![\frac{x}{2},\frac{x}{2},(1\frac{1}{2})\frac{x}{2}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7B2%7D%2C%5Cfrac%7Bx%7D%7B2%7D%2C%281%5Cfrac%7B1%7D%7B2%7D%29%5Cfrac%7Bx%7D%7B2%7D)
Perimeter of the smaller triangle = ![\frac{x}{2}+\frac{x}{2}+(1\frac{1}{2})\frac{x}{2}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7B2%7D%2B%5Cfrac%7Bx%7D%7B2%7D%2B%281%5Cfrac%7B1%7D%7B2%7D%29%5Cfrac%7Bx%7D%7B2%7D)
= x + ![\frac{x}{2}+\frac{x}{4}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7B2%7D%2B%5Cfrac%7Bx%7D%7B4%7D)
= ![\frac{3}{2}x+\frac{x}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B2%7Dx%2B%5Cfrac%7Bx%7D%7B4%7D)
= ![\frac{6}{4}x+\frac{x}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B4%7Dx%2B%5Cfrac%7Bx%7D%7B4%7D)
= ![\frac{7}{4}x](https://tex.z-dn.net/?f=%5Cfrac%7B7%7D%7B4%7Dx)
= 1.75x
Therefore, expression that represents the perimeter of the smaller triangle is (1.75x)
Answer:
C.6
Step-by-step explanation: